Constitutional Analysis of Human Rights Protection Within The Indonesian Legal System - Violla Evarista; Kristanto; Vinanda Langgeng Kencana; Riyan Ardiansyah (International Journal of Law and Legal Ethics, 2025)
This article analyzes the constitutional protection of human rights in Indonesia through the normative framework of the amended 1945 Constitution of the Republic of Indonesia. Human rights protection is positioned as a core element of constitutionalism and the rule of law in a democratic state. Following the Reformasi era, constitutional amendments explicitly incorporated human rights into Chapter XA (Articles 28A–28J), elevating them to the highest legal status. Using a normative legal research method with constitutional, statutory, and conceptual approaches, the article examines the structure, scope, and limitations of constitutional human rights guarantees. The analysis shows that the Constitution provides comprehensive protection of civil, political, economic, social, and cultural rights, reflecting universal human rights norms and national values rooted in Pancasila. Nevertheless, challenges remain in the interpretation, implementation, and enforcement of these guarantees. Special attention is given to Article 28J, which permits limitations on human rights based on morality, religious values, security, and public order. Although constitutionally justified, its broad formulation risks disproportionate restrictions. In this context, the Constitutional Court plays a vital role in safeguarding constitutional supremacy and ensuring proportionality. The article concludes that while Indonesia’s constitutional human rights framework is normatively strong, its effectiveness depends on consistent interpretation, institutional commitment, and a legal culture that genuinely respects human rights.